2003
DOI: 10.14310/horm.2002.1189
|View full text |Cite
|
Sign up to set email alerts
|

The influence of exercise on growth hormone and testosterone in prepubertal and early-pubertal boys

Abstract: The purpose of this study was two fold a) to determine the levels of hormonal parameters which are related to growth and sexual maturation (T, SHBG, .AI, GH) in 66 pre-pubertal and early-pubertal boys (11-13 years old) who systematically engage in individual and team sports activities of endurance, strength, speed and skill, respectively, and b) to investigate the effect of two different forms of exercise namely aerobic (AG) and weight training (WG) on androgen levels in 19 sedentary pre-pubertal boys. The con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Group H showed the highest level of insulin; however, group H had a lower length gain than the FEO-inhaled groups. The FEO-inhaled groups showed lower insulin resistance than group H. A previous study showed that body weight, body fat, and insulin levels were decreased by aerobic exercise, as well as increased GH and IGF-1 levels [27]. According to a previous study and the results of this study, insulin secretion and insulin resistance may indirectly induce an increased length gain, while increasing insulin resistance, which is affected by the excessive secretion of insulin, is one of the inhibitory factors of growth [1,27].…”
Section: Plasma Analysismentioning
confidence: 69%
“…Group H showed the highest level of insulin; however, group H had a lower length gain than the FEO-inhaled groups. The FEO-inhaled groups showed lower insulin resistance than group H. A previous study showed that body weight, body fat, and insulin levels were decreased by aerobic exercise, as well as increased GH and IGF-1 levels [27]. According to a previous study and the results of this study, insulin secretion and insulin resistance may indirectly induce an increased length gain, while increasing insulin resistance, which is affected by the excessive secretion of insulin, is one of the inhibitory factors of growth [1,27].…”
Section: Plasma Analysismentioning
confidence: 69%
“…These results are in accordance with previous studies that observed no change in the basal plasma free testosterone and TT concentrations after resistance training in adolescent handball [11] and soccer players [12] . However, others studies have also reported an elevation of the basal TT levels in adolescent males in response to shorter physical training programs (i. e., 2 -3 months) that included heavy resistance training [34] and intense endurance training sessions [35] . These latter results suggest that training intensity and volume in our study would be insuffi cient to increase basal plasma testosterone concentrations.…”
Section: Discussion ▼mentioning
confidence: 96%
“…According to Hartley (1975) and Bunt et al (1986), GH levels increase during training period. Tsolakis et al (2003) found significant differences in T and GH among athletes group (handball, rowing, running, basketball, fencing etc.). The mean T of the control group (sedentary boys) did not differ from those of the corresponding exercise group.…”
Section: Discussionmentioning
confidence: 86%
“…The mean T of the control group (sedentary boys) did not differ from those of the corresponding exercise group. The study by Tsolakis et al (2003) demonstrated the importance of the specificity of the training stimulus in the hormonal adaptations of pre-pubertal sedentary subjects.…”
Section: Discussionmentioning
confidence: 99%